An Analysis of Students’ Achievement in Reading Comprehension at the Tenth Grade of SMKN 1 Rejotangan - Vitria Candra Dewi; Ika Rahmawati (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
To read something especially long text in foreign language, students usually have problems, for example lazy and bored. If this problem still continues, it will give affect for students’ achievement. This research aims to find out how is the tenth grade students' achievement in reading comprehension at SMK 1 Rejotangan in the academic year 2018/2019. The researcher used qualitative methods to obtain valid data from 37 tenth grade student participants in X-AP2 class. The researcher obtained data of reading comprehension test scores from teachers with an average grade of 55, with minimum criteria score of 75. To test the validity, researchers conducted interviews with teachers and students, questionnaires that answered by students, and observations of teaching and learning activities on reading comprehension. After re-analyzed, it can be concluded that the learning of reading comprehension in the recount text, students get low achievement. They have problems caused by themselves, they have difficulty in understanding the contents of the text, limited of vocabulary, and they lack motivation to learn.